CP-137 Invasive fungal infections: Observational study in two hospitals in italy (TURIN) and france (PARIS). (14th February 2016) - Tullio, V; Tarantini, R; Roana, J; Fucale, G; Tilleul, P; Crosasso, P; Castellana, E; Allizond, V; Mandras, N
Abstract : Background: Invasive fungal infections (IFIs) constitute a frequent and important complication in modern medicine and represent a relevant problem in the matter of the management of hospitalised and immunocompromised patients. The most common fungal infections, candidiasis and aspergillosis, are an important cause of morbidity and mortality in critically ill and immunocompromised patients: therefore, in spite of pharmacological development, they are still difficult to treat and to eradicate. Purpose: Because the pharmacist, as a member of the multidisciplinary team, can contribute by checking the treatment prescribed, to reduce medication related problems, we conducted an observational study of IFIs in two hospitals, one in Italy (Turin) and the other in France (Paris), to give a picture of the differences in their distribution and therapeutic approach in two hospital realities. Material and methods: The study was conducted using a clinical database of patients between 2012 and 2013; patients were stratified according to infection, sex, age, wards and therapy. Results: Candida or aspergillus related IFIs were detected in 213 men and 107 women. Candidiasis was higher in the critical care unit (Turin 40% vs Paris 48%), prevalent in men Turin 78%; Paris 65%) and older patients (61–90 years old), with a prevalence of 67% in Turin and 49% in Paris. In France, aspergillosis was highly distributed in the critical care unit (42%) and in the haematology ward (38%), was prevalent in men (68%) and, unlike candidiasis, in younger patients (47%; 31–60 years old). A comparable study was not possible for Turin where only one systemic aspergillosis was diagnosed. The most widely used drug in both hospitals was caspofungin, followed by fluconazole in Turin and voriconazole in Paris. Conclusion: A similar trend in candidiasis related IFIs, with no significant differences between the two hospitals, was detected. Conversely, there were differences in the use of drugs. To reduce the incidence and mortality rate of IFI, the therapeutic approach should take account of the epidemiological picture but the hospital pharmacist's role is also important. In fact, the hospital pharmacist together with the hospital infections committee, can monitor and analyse consumption, perform epidemiological statistics and choose the best therapy for patients in terms of cost and efficacy. No conflict of interest.